Realizing Idioms in Conversational Texts of English Textbooks for Eleventh Graders - Hanum Bestari; Sri Wuli Fitriati; Dwi Rukmini (Language Circle: Journal of Language and Literature, 2025)
This study focuses on how idioms are realized in conversational texts of English textbooks for the eleventh year: English for Change and Bahasa Inggris Tingkat Lanjut. The textbooks were published concerning the Emancipated Curriculum (Kurikulum Merdeka) in Indonesia which focuses on learners’ autonomy and real-life communication. Therefore, examining how well educational materials support these goals is essential. The idioms were identified as one of the formulaic expressions categorized using Biber et al. (1999). To conduct and produce the results, the researcher plays a role in collecting, analyzing, interpreting, grouping data into codes, and concluding collected data. By employing a descriptive analysis of the conversational texts from the selected textbooks, this study contributes to the understanding of pedagogical approaches to teaching conversational language. It offers insights for educators, curriculum developers, and textbook authors. The findings showed that the types of idioms realized from the textbooks are phrasal verbs (15 data), prepositional verbs (2 data), and phrasal-prepositional verbs (3 data). Nevertheless, no data was found for multi-word verb combinations. Understanding idioms is important for good communication because it helps to better understand the language, express ourselves more clearly, and learn about different cultures.